Viral Proteins Mediate Upregulation of Negative Regulatory Factors Causing Down-Modulated Dendritic Cell Functions In Chronic Hepatitis C Virus Infection - Deepa Rana (European Medical Journal Hepatology, 2013)
Stunted cellular immune response against a narrow range of epitopes is the hallmark of chronic hepatitis C infection, but the underneath molecular mechanisms have not been well elucidated. Suboptimal antigen presentation through defective antigen presenting cells, have been suggested. The myeloid dendritic cells as professional antigen presenting cells have been found to be phenotypically and functionally defective in chronic hepatitis C-infected patients in our recently published study. In order to find out if the maturation defects in dendritic cells (DC) are induced by the persistence of virus, we tried to differentiate CD14+ monocytes isolated from the peripheral blood of a healthy volunteer in dendritic cell culture medium containing GM-CSF and IL-4 supplemented with hepatitis C virus (HCV) proteins, core and NS5. The results indicated that a lesser number of monocytes differentiated to DC in presence of HCV proteins. Moreover, the differentiated cells depicted immature phenotype, which will not respond to the TLR-4 mediated stimulation ex vivo with significantly lesser upregulation of activation markers, HLA-DR, CD83, CD80 and CD86 as compared to cells differentiated in the absence of HCV proteins. Besides, these immature cells showed characteristics of defective antigen presentation, with significantly lower allostimulatory capacity towards lymphocytes from a healthy donor. Semi-quantitative reverse-transcription polymerase chain reaction (RT- PCR) showed upregulated expression of negative regulatory genes SOCS3, PDL1 and IDO in cells grown in presence of HCV proteins, suggesting the role of HCV and associated antigens in functional down- modulation of dendritic cells. This may correlate with the antigen persistence and maturation-defective status of dendritic cells in chronic HCV infection.